'Single‐handed care' initiatives and reviews of double‐handed homecare packages: A survey of practices in English local authorities with adult social care responsibilities. (1st September 2022) - Whitehead, Phillip J.; Rooney, Leigh; Adams‐Thomas, Jane; Bailey, Catherine; Greenup, Marie; Southall, Carole; Raffle, Anne; Rapley, Tim; Whittington, Stephanie
Abstract: International health and social care systems are experiencing unprecedented pressure and demand. 'Single‐handed care' initiatives seek to identify whether all or part of a homecare package involving more than one care worker can be safely reduced to a single worker. Little is known about these initiatives across local authorities. The aim of this study was to identify, describe and explain current processes and practices for single‐handed care initiatives and double‐handed homecare reviews. An electronic survey link was sent to each local authority with social care responsibilities in England. The questions covered a range of areas in relation to single‐handed care processes and included a combination of pre‐coded and free‐text responses. Responses were received from 76 (50%) local authorities. Findings were that over 12, 000 reviews were reported within a year with a median of 141 (IQR 45–280) from 53 authorities that provided figures. Reviews were usually led by a local authority occupational therapist. On average, 540 min was spent per review, including conducting and organising the review, documentation, and travel. In nearly half the authorities, double handed care remained at least partially in place following at least 80% of the reviews and remained wholly in place following at least 60%. Local authorities also reported some resistance from homecare providers when implementing single‐handed care. The findings have confirmed anecdotal evidence that reviews of double‐handed homecare packages are common practice within local authorities. Given the amount of time taken with these reviews, and paucity of evidence on outcomes for people receiving them, further research should evaluate this.